Hukum pembuktian dalam sengketa tata usah negara (UU No.5 Th.1986, LN No.77) - PRODJOHAMIDJOJO, Martiman (Pradnya Paramita, 1997)
Hukum pembuktian. Dalam sengketa tata usaha negara (UU No.5 Th.1986, LN No.77)